2016
DOI: 10.1371/journal.pone.0149493
|View full text |Cite
|
Sign up to set email alerts
|

An Allometric Modelling Approach to Identify the Optimal Body Shape Associated with, and Differences between Brazilian and Peruvian Youth Motor Performance

Abstract: Children from developed and developing countries differ in their body size and shape due to marked differences across their life history caused by social, economic and cultural differences which are also linked to their motor performance (MP). We used allometric models to identify size/shape characteristics associated with MP tests between Brazilian and Peruvian schoolchildren. A total of 4,560 subjects, 2,385 girls and 2,175 boys aged 9–15 years were studied. Height and weight were measured; biological matura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Instead, differences were amplified, likely because the more favorable body dimensions of Tanzanians. [15, 24, 25] Prista et al[26] highlighted the importance of physical activity to the development of aerobic fitness in Mozambique youth. The superior aerobic fitness of rural children has also been attributed to a lifestyle that is more physically active than that of urban dwellers.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, differences were amplified, likely because the more favorable body dimensions of Tanzanians. [15, 24, 25] Prista et al[26] highlighted the importance of physical activity to the development of aerobic fitness in Mozambique youth. The superior aerobic fitness of rural children has also been attributed to a lifestyle that is more physically active than that of urban dwellers.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, Silva et al recently reported an association between hand-grip strength, body mass, body height, and PA levels in youth. The authors found that performance on these measures was positively related with greater body mass (probably muscle mass) and greater height (probably reflecting greater leverage) and only partially related with PA levels [ 64 ]. Collectively, these findings can indirectly explain the lack of association found in our study between latent class 2 and low upper body maximal strength ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The variation in children's stature associated with SES results in difficulty interpreting the between‐group differences in BMI (Monyeki et al, ; Sandercock et al, ; Silva et al, ). The model used to predict handgrip included positive exponents for both body mass and stature, as shown previously in studies of South American (Silva et al, ), European (Nevill, Tsiotra, Tsimeas, & Koutedakis, ; Tambalis, Panagiotakos, & Sidossis, ) and African (Dos Santos et al, ) youth. The importance of appropriate scaling when comparing cohorts of different body size is also highlighted in a recent cross‐cultural comparison showing higher absolute handgrip values in youth from Portugal compared with Mozambique (Dos Santos et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how best to scale measures such as muscular fitness is important for researchers and policy makers in public health, education, and the exercise sciences (Nevill, Ramsbottom, & Williams, ). Appropriate scaling helps ensure valid inferences can be made when investigating physiological differences in populations that also differ in terms of body size (Silva et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation